Improvement To Shunt Contactors for External Floating Roof Tank Lightning Protection System - Mohd Yusri B. Mohd Yusoff, Mohd Yusri (Universiti Teknologi Petronas, 2010)
This project is to prevent the formation of electrical spark during a lightning strike; this is one of the main causes of rim fire on an external floating roof tank. During my internship at Petronas Penapisan Terengganu Sdn. Bhd. (PPTSB), the engineers are trying to prevent more fire incident from occurring on their floating roof tank that are used to store highly volatile petroleum products. The sparking is caused by the gap between the contact shunt and the tank wall. When the tank roof a stroked by lightning the shunt should provide a low resistance path to conduct the high current, but if a gap exist between them spark will be produce. To make things worse the current design of floating roof tank has place this contact at a location that has high flammable gas concentration. In this project, I will attempt to improve the design on the current shunt contactors so that no gap will be formed between it and the tank wall. At the end of this project, I will fabricate a scaled to show how it will work. I will test it against a conductive wall (metal or steel) using high voltage source to see whether any sparking occurs.